AN ANALYSIS CAUSES OF LINE DISTURBANCE IN ELECTRICITY DISTRIBUTION IN PT. PLN (PERSERO), ULP EAST BINJAI - Eky Firdian Fauzi; Siti Anisah; Hamdani Hamdani (INFOKUM, 2022)
The distribution line is the section of the electricity line that is closest to the community; it is divided into two parts: primary and secondary distribution lines. PLN primary distribution voltages are 20 KV, 12 KV, and 6 KV. The primary distribution voltage that PLN typically produces is 20 kV. The purpose of this study is to use FTA to determine the main causes of disturbances in the electricity distribution line at ULP Binjai Timur (Fault Tree Analysis). The large difference between the electrical energy sent from the substation and the electrical energy obtained from customer consumption demonstrates the study's findings. The following are the causes of these disturbances: component JTM (I1) with as many as 55 faults (12.5 percent), JTM equipment (I2) with as many as 30 faults (6.7 percent), transformer faults (I3) with as many as 8 faults (1.8 percent), natural disturbances (I4) as many as 1 disturbance (0.2 percent), external disturbances (E1) as many as 15 disturbances (3 percent), natural disasters (E2) as many as 61 disturbances (13.7 percent), the work of other parties/animals (58.2 percent). After conducting research on the causes of disturbances in the electricity distribution line at ULP Binjai Timur and analyzing the data with Fault Tree Analysis (FTA), it was discovered that the main cause of disturbance is a human disturbance, manifested as kites, banners, and digging PDAM channels